Calculation of Foundation Structure and Design Planning of The Building of The Faculty of Civil Engineering and Planning, Gunung Jati University, Cirebon - Wikal Tyas Adhiwiyatno; Trio Galih Hartaro; Yoga Pamungkas; Sumarman Sumarman (Journal of World Science, 2025)
The "Guidelines for Planning House and Building Loads", "Minimum Loads for Designing Buildings and Other Structures", "Procedures for Planning Earthquake Resistance for Building and Non-Building Structures", and "Structural Concrete Requirements for Buildings and Their Explanations" serve as the guidelines in order to structural examination planning as well as layout of UGJ Property. Constructural drawing as well as structural analysis programs are accustomed to ascertain the seismic period of the constructure and the internal forces acting on it. The reinforcing steel utilized has a quality of 420 MPa, while the concrete material used has a quality of 30 MPa. A bored pile foundation of 4 m depth was selected based on the planning results. Keyword: Design, Faculty, Foundation, Planning, Structure.